Tanggungjawab Yuridis PT. Tokopedia atas Kebocoran Data Pribadi dan Privasi Konsumen dalam Transaksi Online - Alfrida Sylfia; i Gusti Ngurah Adyana; Mohammad Fahrial Amrullah; Hendra Djaja (University of Merdeka Malang, 2021)
The development of information technology which is increasingly advanced and developing rapidly has caused everyone to easily carry out various online transactions using electronic media without any limitations in space and time. With this progress, it creates new problems in electronic systems that cause leakage of personal data andconsumer privacy. Such as experienced by business company, PT. Toko Pedia. This approach focuses on examining literature materials such as statutory regulations and other relevant sources. This study examines how the legal relationship between consumers and PT. Toko Pedia as well as how the responsibilities of PT. Toko Pedia if there is a leak of personal data and consumer privacy. This study uses a normativejuridical approach. The results of this study are to provide an understanding of perotecting personal data and consumer privacy, the efforts if there is a leak of personal data and consumer privacy, the penalty and responsibilities that business company accept of leaking the consumer privacy and personal data.